Building in the past a preliminary analysis of the construction materials and methods used in structure a in Barangay Pinagbayanan, San Juan, Batangas - Sales, Angelus Maria P. (2013)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/3965/3611
Keywords: Archaeological research; Construction materials; Building design and construction